Understanding challenges in informal leadership mentoring: voices from Malaysian deputy primary schools / Lokman Mohd Tahir ... [et al.] - Mohd Tahir, Lokman; Abdul Aziz, Norazah; Ahmad, Roslee; Ali, Mohd Fadzli; Hamzah, Lina Mursyidah; Hasnor, Hanin Naziha (Universiti Teknologi MARA, 2024)
Due to the lack of support and preparation received by deputy principals, the school principals were assigned to provide their informal mentoring with the purpose of enhancing DPs’ leadership skills and knowledge. Admittedly, some challenges and barriers decrease and lessen the effectiveness of informal mentoring between DPs and their principals, which previously received little attention. The primary aim of this study is to identify the main challenges and barriers faced by DPs in participating in informal mentoring with their principals. A total of 318 primary deputies were asked to respond to a questionnaire. In addition, 12 DPs were purposely selected to capture the in-depth reasons related to their challenges and barriers in informal mentoring. As predicted, the lack of time due to their heavy workload has lessened the effectiveness of informal mentoring in schools. Besides, disagreement between DPs and principals, lack of explanations from principals, and issues with principals’ trust are the other challenges DPs and principals face while engaging in informal mentoring. The challenges were selected by DPs and later highlighted by DPs during interview sessions. To overcome the challenges, a few suggestions were forwarded to improve the informal mentoring practices.